2014
DOI: 10.18632/oncotarget.1840
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of actionable mutations to histological subtype domains in lung adenocarcinoma: implications for precision medicine

Abstract: Precision medicine depends on the accurate identification of actionable mutations in a tumor sample. It is unknown how heterogeneous the distribution of such mutations can be in a tumor. Morphological (i.e. histopathological) heterogeneity is well described in lung adenocarcinoma and has been specifically recognized in the most recent official clinico-pathological classification. The most predominant subtype present is now used to classify each lung adenocarcinoma. No molecular profile exists to explain the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…analysis has been demonstrated to be useful for the diagnosis of lung adenocarcinoma (45) and Moroccan breast cancer (46); Studies using HRM analysis showed heterozygous mutations in COL1A1 and COL1A2 genes are associated with osteogenesis imperfecta (47).…”
Section: Discussionmentioning
confidence: 99%
“…analysis has been demonstrated to be useful for the diagnosis of lung adenocarcinoma (45) and Moroccan breast cancer (46); Studies using HRM analysis showed heterozygous mutations in COL1A1 and COL1A2 genes are associated with osteogenesis imperfecta (47).…”
Section: Discussionmentioning
confidence: 99%
“…ALK translocations are more prone to be identified in lung adenocarcinomas and in acinar, solid and signet cell morphology [45,[48][49][50]. However, there are some conflicting results as some authors identify EGFR mutations in all the patterns of lung adenocarcinomas; these authors identified an association of KRAS and BRAF mutations and high nuclear grade [51].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with epidermal growth factor receptor ( EGFR )‐activated mutation or anaplastic lymphoma kinase ( ALK ) fusion obtain significant benefit from targeted therapy with small molecule tyrosine kinase inhibitors (TKIs) . With the completion of genomic analysis in lung cancer by The Cancer Genome Atlas (TCGA) Research Network , more and more sensitizing molecular alterations have been identified in genes such as KRAS, ROS1, RET, BRAF , HER2, MET exon 14 , and PIK3CA that could potentially be targeted in NSCLC .…”
Section: Introductionmentioning
confidence: 99%